Digital Transformation in Banking Management: Optimizing Operational Efficiency and Enhancing Customer Experience - Alam, Yuli; Azizah , Siti Nur; Caroline, Caroline (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Digital transformation in the banking sector has become a fundamental phenomenon, fundamentally changing how banks operate and interact with customers. The adoption of digital technologies across various operational aspects of banks, from internal processes to customer services, has the potential to improve efficiency and deliver a better customer experience. The primary objective of this study is to analyze the impact of digital transformation on operational efficiency and the enhancement of service quality in the banking sector. This research also focuses on identifying the challenges and opportunities banks face during digitization. In their pursuit of greater efficiency, banks are integrating various technologies such as process automation, big data, artificial intelligence (AI), and cloud-based systems to replace previously used manual methods. This reduces operational costs and improves speed, accuracy, and consistency in service delivery. However, implementing these technologies requires adequate infrastructure readiness, skilled human resources, and a shift in organizational culture to support adopting new technologies. This study reveals that banks implementing digital transformation can experience increased productivity and competitiveness. However, challenges related to initial investments, resistance to change, and the management of technological risks remain significant barriers that must be addressed. The research offers valuable insights for banks planning digital transformation and stakeholders developing technology-driven banking policies.